2015
DOI: 10.4314/pelj.v18i3.02
|View full text |Cite
|
Sign up to set email alerts
|

Selected Legal Challenges Relating to the Military use of Outer Space, with Specific Reference to Article IV of the Outer Space Treaty

Abstract: It's politically sensitive, but it's going to happen. Some people don't want to hear this, and it sure isn't vogue, but-absolutely-we're going to fight in space. We're going to fight from space and we're going to fight into space. That's why the US has developed programs in directed energy and hit-to-kill mechanisms. We will engage terrestrial targets someday-ships, airplanes, land targets-from space. 12 The USA regards outer space as a top national security interest to which its military power should be exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 2 publications
0
10
0
1
Order By: Relevance
“…Concerning the moons, it is suggested that a decision should be taken on a political level due to the various types of moons and the fact that they have gravity wells of their own and are situated within the overall gravity well of their parent planets. 6 Additionally, it is not only interesting to see how the Outer Space Treaty influences the rights and responsibilities of humans and robots in today's law but also how this may influence and provoke changes in international regulations in the future. Reflections are undertaken to consider including an appropriate section of robotic law in the OST in order to take into account the fact that some nations consider giving "personhood" status to robots.…”
Section: Executive Summarymentioning
confidence: 99%
See 4 more Smart Citations
“…Concerning the moons, it is suggested that a decision should be taken on a political level due to the various types of moons and the fact that they have gravity wells of their own and are situated within the overall gravity well of their parent planets. 6 Additionally, it is not only interesting to see how the Outer Space Treaty influences the rights and responsibilities of humans and robots in today's law but also how this may influence and provoke changes in international regulations in the future. Reflections are undertaken to consider including an appropriate section of robotic law in the OST in order to take into account the fact that some nations consider giving "personhood" status to robots.…”
Section: Executive Summarymentioning
confidence: 99%
“…5 In addition, the Security Council can decide what measures should be taken in order to maintain or restore international peace and security. 6 On the one hand, the Security Council may decide to take measures that do not involve the use of armed forces; this may include complete or partial interruptions of economic relations and of rail, sea, air, postal, telegraphic, radio and other means of communication and the severance of diplomatic relations. 7…”
Section: International Peace and Security Under Un Chartermentioning
confidence: 99%
See 3 more Smart Citations